THE EFFECT OF PROMOTION AND SERVICE QUALITY ON CONSUMER SATISFACTION AT BEAUTIFUL STALLS IN CEMAGI VILLAGE, BADUNG - Ni Made Wulan Purnama Juliani; Ni Wayan Widi Astuti; Putu Siti Firmani (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2024)
Based on observations made at Warung Cantik in Cemagi Village, Badung. The lowest number of consumers occurred in 2020 was 12,515, while the highest number of consumers in 2021 was 14,954. This study aims to determine the influence of promotion and service quality on consumer satisfaction at Warung Cantik in Cemagi Village, Badung. This study uses a causal associative quantitative approach through observation, interview, questionnaire and documentation methods that take 100 consumer respondents. The results of this study show that (1) There is a partially significant influence between promotion variables on consumer satisfaction as evidenced by the results of the tally test 8.165> ttable 1.98 with a significant value (0.000 < 0.05); (2) There is a partially significant influence between the variables of service quality on consumer satisfaction as evidenced by the results of the tcount test of 10.864 > ttable 1.98 with significant values (0.00 < 0.05); (3) There is a simultaneous significant influence between promotion variables and service quality on consumer satisfaction as seen from the results of the Fcal test of 96.223 > Ftable 3.09 with a significant value (0.000 < 0.05). The results of the determination coefficient show that the size of the Adjusted R Square is 0.665, which means that 66.5% of the variation in consumer satisfaction is influenced by promotion and service quality, while the remaining 33.5% is influenced by other factors